Analisis Kepuasan Pelayanan dan Literasi TIK Pengunjung Dinas-Dinas di Kota Bogor - Ryska Putri Madyasari; Anang Kurnia; Rahma Anisa; Yani Nurhadryani (Xplore: Journal of Statistics, 2019)
Determining Public Satisfaction Index using analysis of Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) can be utilized to improve service quality of Governmental Departments in X City. Analysis of IPA and CSI were used to measure the level of respondents’ satisfaction regarding the provided services. The departments were selected using purposive sampling method. Four selected departments were Population and Civil Registry Department, Transportation Department, Housing and Settlement Department, and Social Department. The result showed that customers were moderately satisfied with the services, with the following CSI index value: 70.09%, 72.95%, and 76.61% respectively for each departments. Moreover, Social Department’s customers were very satisfied with the CSI index 81.56%. In this study, aspect of Information and Communication Technology (ICT) literacy indicator were more exposing the ability to operate personal computer. There were six indicator of ICT literacy, i.e access, manage, integrate, evaluate, create, and communication. The value of evaluate indicator were quite high, it has reached score higher than 50% for each departments were. However, based on overall score, it was shown that 60% respondents still have low ICT literacy. This study also showed that ICT literacy were related to responden’s education and age. It increased along with the higher level of education that has been completed by respondents, and with the age of 17-39 years old.